RELATIONSHIP BETWEEN DEHYDRATION WITH WORKING WORK ON SAND CARRIER WORKERS IN DEPOT PASIR MUTIARA - Ratno Purnamasari (Sriwijaya University Learning and Education International Conference, 2018)
Background: Hot working environment could increase heat stress occurrence on workersthat could cause dehydration and working fatigue. This study aims to analyze therelationship between dehydration and working fatigue on sand transport workers inMutiara Sand Depot. Method: This study is a cross sectional study with sand transportworkers in Mutiara Sand Depot as sample. Sample consist of 65 workers with inclusioncriteria workers whom had work for more than 2 years and permanent employee.Dehydration measurement done by using urine color examination that taken afterworking, meanwhile working fatigue measured based on working fatigue analysis usingSubjective Self Rating questionnaire (SSRT). Data analyzed by using chi-square test.Result: Based on urine color examination almost all of the workers (95%) weredehydrated, only 5% of the workers were not dehydrated. Working fatigue measurementshows that most of workers (89%) experienced minor fatigue, 10% experienced fatigue,and only 1% experienced major fatigue. Chi-Square test shows that there is a significantrelationship between dehydration and working fatigue (p=0,00). Conclusion: dehydrationhave relationship with working fatigue on sand transport workers in Mutiara Sand Depot.